A new strategy for the decellularization of whole organs by hydrostatic pressure. (3rd March 2022) - Morales‐Guerrero, Nelly A.; Varela‐Echavarría, Alfredo; Lozano‐Flores, Carlos; Vázquez‐Cuevas, Francisco G.; Velázquez‐Miranda, Erandi; Reyes‐López, Julián V.; García‐Solís, Pablo; Solís‐S, Juan Carlos; Hernandez‐Montiel, Hebert Luis
Abstract: Tissue engineering has been able to develop novel decellularization‐recellularization techniques, which facilitates the research for the generation of functional organs. This is based in the initial obtention of the organ's extracellular matrix (ECM). Therefore, any improvement in the decellularization process would have a positive impact in the results of the recellularization process. Nevertheless, commonly the methods and equipment employed for this process are expensive and thus limit the access of this technique to various research groups globally. To develop a decellularization technique with the exclusive use of hydrostatic pressure of detergent solutions, to have an easily accessible and low‐cost technique that meets the basic requirements of acellularity and functionality of the ECM. This experimental study was performed in 10 male Wistar rats, obtaining the liver to carry out serial washes, with 1%, 2%, and 3% Triton X‐100 solutions and 0.1% SDS. The washes were performed by using a gravity perfusion system (GPS), which assured us a continuous hydrostatic pressure of 7.5 mmHg. The obtained ECM was processed using stains and immunostaining to determine the residual cell content and preservation of its components. The staining showed a removal of cellular and nuclear components of approximately 97% of the acellular ECM, with an adequate three‐dimensional pattern of collagen and proteoglycans. Furthermore, the acellular ECM allowed the viability of a primary hepatocyte culture. The use of the GPS decellularization technique allowed us to obtain an acellular and functional ECM, drastically reducing experimentation costs.